Solute Carrier Family 12 Member 2 as a Proteomic and Histological Biomarker of Dysplasia and Neoplasia in Ulcerative Colitis. (13th September 2020) - Merli, Angela-Maria; Vieujean, Sophie; Massot, Charlotte; Blétard, Noella; Quesada Calvo, Florence; Baiwir, Dominique; Mazzucchelli, Gabriel; Servais, Laurence; Wéra, Odile; Oury, Cécile; de Leval, Laurence; Sempoux, Christine; et al.
Abstract: Background and Aims: Ulcerative colitis [UC] patients have a greater risk of developing colorectal cancer through inflammation-dysplasia-carcinoma sequence of transformation. The histopathological diagnosis of dysplasia is therefore of critical clinical relevance, but dysplasia may be difficult to distinguish from inflammatory changes. Methods: A proteomic pilot study on five UC colorectal dysplastic patients highlighted proteins differentially distributed between paired dysplastic, inflammatory, and normal tissues. The best candidate marker was selected and immunohistochemistry confirmation was performed on azoxymethane/dextran sulphate sodium [AOM/DSS] mouse model lesions, 37 UC-dysplasias, 14 UC-cancers, 23 cases of long-standing UC, 35 sporadic conventional adenomas, 57 sporadic serrated lesions, and 82 sporadic colorectal cancers. Results: Differential proteomics found 11 proteins significantly more abundant in dysplasia compared with inflammation, including Solute carrier family 12 member 2 [SLC12A2] which was confidently identified with eight specific peptides and was below the limit of quantitation in both inflammatory and normal colon. SLC12A2 immunohistochemical analysis confirmed the discrimination of preneoplastic and neoplastic lesions from inflammatory lesions in mice, in UC, and in sporadic contexts. A specific SLC12A2 staining pattern termed 'loss of gradient' reached 89% sensitivity, 95% specificity, and 92% accuracy for UC-dysplasia diagnosis together with an inter-observer agreement of 95.24% [multirater κ free of 0.90; 95% CI: 0.78 - 1.00]. Such discrimination could not be obtained by Ki67 staining. This specific pattern was also associated with sporadic colorectal adenomas and cancers. Conclusions: We found a specific SLC12A2 immunohistochemical staining pattern in precancerous and cancerous colonic UC lesions which could be helpful for diagnosing dysplasia and cancer in UC and non-UC patients.